The role of telehealth in pediatric emergency care - Mohsen Saidinejad; Isabel Barata; Ashley Foster; Timothy K. Ruttan; Muhammad Waseem; Douglas K. Holtzman; Lee S. Benjamin; Sam Shahid; Kathleen Berg; Dina Wallin; Shireen M. Atabaki; Madeline M. Joseph; et al. (Journal of the American College of Emergency Physicians Open)
Abstract In 2006, the Institute of Medicine published a report titled “Emergency Care for Children: Growing Pains,” in which it described pediatric emergency care as uneven at best. Since then, telehealth has emerged as one of the great equalizers in care of children, particularly for those in rural and underresourced communities. Clinicians in these settings may lack pediatric‐specific specialization or experience in caring for critically ill or injured children. Telehealth consultation can provide timely and safe management for many medical problems in children and can prevent many unnecessary and often long transport to a pediatric center while avoiding delays in care, especially for time‐sensitive and acute interventions. Telehealth is an important component of pediatric readiness of hospitals and is a valuable tool in facilitating health care access in low resourced and critical access areas. This paper provides an overview of meaningful applications of telehealth programs in pediatric emergency medicine, discusses the impact of the COVID‐19 pandemic on these services, and highlights challenges in setting up, adopting, and maintaining telehealth services.